Design and Optimisation of a Pedestrian-Power Piezoelectric Energy Harvesting System - Mat Zian@ Mat Zin, Ahmad Faiz; Asril Rajo Mantari, Muhammad Hanafi; Wan Mohd Nasir, Wan Musyrif; Wan Ahmad, Wan Nor Alieya Maisara; Wong , Nyuk Cheng; Kamaruddin, Syamsul Azrin (Multidisciplinary Applied Research and Innovation, 2025)
This study presents a pedestrian-powered piezoelectric energy harvesting system that generates renewable electricity from human footfalls. The device uses piezoelectric transducers (PZT) arranged in series and parallel configurations for maximum voltage output, alongside a full-wave bridge rectifier and a battery management system (BMS) for efficient energy storage. Experimental results show that a series circuit of 40 piezoelectric sensors achieves a peak AC voltage of 5.5 V and an average output of 1.9 VAC during operation. Testing user weights of 43 to 77 kg and different spring configurations showed that series connections produced up to 5.5 VAC, outperforming parallel setups. Dual-spring mechanisms further enhanced voltage output by improving force transmission. Innovations include low-cost plywood for structural integrity and 3D-printed polylactic acid (PLA) pressers to enhance force transmission. The harvested energy is stored in a lithium-ion battery, highlighting its potential for low-power urban infrastructure applications. This work promotes sustainable energy solutions by improving scalability, cost-effectiveness, and efficiency in piezoelectric energy harvesting, with future recommendations focused on enhancing transducer density and mechanical design.